GENDER DISPARITY IN PAKISTANI MEDIA ORGANIZATIONS IN THE DIGITAL AGE - Mirza, Zainab Kamran (PEOPLE: International Journal of Social Sciences, 2016)
This study analyses gender inequality and glass ceiling, which are the greatest hindrances that are keeping away the Pakistani women from reaching high positions in the media organizations. Working women in Pakistan face much difficulty in climbing the professional ladder and are regularly discriminated from the leadership positions. The study at hand, investigates the overarching circumstance of discriminatory limitation impact from Pakistani working women's viewpoint alongside limited career opportunities that are keeping them away from profession about which they are ambitious. The gender discrimination is accessed on five categories: Glass ceiling, Wage gap, opportunities, Competence, Social and cultural barriers. Survey questionnaire was given to 30 working female reporters, journalists and RJ’s. Findings offered insight about the prevalence of gender discrimination in media jobs targeted to females. Women can fantasize only however, might never achieve high stature positions in media organizations. It's certainly wrong to say that women are not competent enough and lack the skills and don't have the right capacities to be deserving of key posts in media.